Parihaka-tecture - Wood, Peter (Architectural History Aotearoa, 2021)
At 5.00am of November the 5th, 1881, government-sanctioned troops entered the Taranaki Pā of Parihaka, arresting key leaders, expelling occupants and destroying the buildings. The impetus for the assault was highly political. On the one hand Parihaka represented a focus for a broad fear of Māori political independence. At the same time the demand for fertile farm land by colonial settlers was not being met. Scattering the people of Parihaka was a central strategy for alleviating the former and satisfying the latter. Similarly, the destruction of the material fabric of the village – its architecture – was a purposeful action designed to erase any legitimate presence over the land. Not until the publication of Dick Scott's The Parihaka Story, in 1954, were the events of Parihaka brought to a wider Pākehā audience. Today it is largely, and correctly, understood as a particularly ugly moment in our history. However, while we may have developed a certain social self-consciousness toward the racial and political ramifications of Parihaka, not enough has been made of the extraordinary architecture that framed it. In this paper I wish to add to what we do know by reviewing period photographs of Parihaka Pā at the time of the invasion. In particular, I will be giving consideration to Miti-mai-te-arera (the house of Te Whiti), Rangi Kapuia (the house of Tohu), Nuku-tewhatewha (the communal bank) and Te Niho-o-Te-Ātiawa (the dining hall). It is my view that the colonial government were right to interpret these prominent buildings as symbolically threatening and in this paper I hope to show why they were so, but also how their presence nonetheless continued well into the twentieth century.